The cultural contribution of women in the Medieval Islamic du ringreign if the Almohads - menfoukh, Dahbiya; benbouzid, Lakhdar (The Algerian Historical Journal, 2026)
Women have always been an effective element in the country's development, progress, and prosperity, and their great work has appeared since the early ages of the history of themedieval Islamic, especially during the Almohad era, where women took the lead in advancement, as they contributed to intellectual activity, literary and scientific. In this era, women received an abundant share of education through... The compulsory education system approved by Caliph Abd al-Mu’min bin Ali made it compulsory for men and women. This opened the door for her to participate in scientific life, and a number of women appeared who were known for their ease and the power of insight, and who had an unlimited share in enriching the ancient Islamic history with a series of gatherings, deeds, and sayings. They were poets. Some of them surpassed men, such as Hafsabint al-Hajj al-Rakuliyya, and righteous jurists such as Khayrunah al-Qasi, and other women who had an effective role in the prosperity of life Cultura.